The cardiovascular effect of incretin-based therapies among type 2 diabetes: a systematic review and network meta-analysis - Wu, S; Cipriani, A; Yang, Z; Yang, J; Cai, T; Xu, Y; Quan, X; Zhang, Y; Chai, S; Sun, F; Zhan, S (Taylor and Francis, 2018)
Objective: To evaluate the comparative cardiovascular safety of incretin-based therapies in patients with type 2 diabetes mellitus (T2DM). Methods: Medline, Embase, the Cochrane Library and www.clinicaltrials.gov were searched for randomized controlled trials (RCTs) with duration≥12 weeks. Network meta-analysis was performed, followed by subgroup analysis and meta-regression. The Grading of Recommendations Assessment, Development and Evaluation system was used to assess the quality of evidence. The outcome of interest was a composite of cardiovascular death, myocardial infarction, stroke and heart failure. Odds ratio (OR) with 95% confidence interval (CI) was calculated as the measure of effect size. Results: 281 RCTs (76.9% double-blinded) with 180,000 patients were included, comparing incretin-based therapies with other six classes of anti-diabetic drugs or placebo. A statistically significant reduction in the risk of cardiovascular events was found in favour of GLP-1RAs when compared with placebo (OR 0.89, 95%CI: 0.80–0.99) and sulfonylurea (OR 0.76, 95%CI: 0.59–0.99), whereas DPP-4 inhibitors showed a neutral effect compared with placebo (OR 0.92, 95%CI: 0.83–1.01). Conclusions: Incretin-based therapies show similar cardiovascular risk in comparison with metformin, insulin, thiazolidinediones, alpha-glucosidase inhibitor and sodium-glucose co-transporter 2. GLP-1RA could decrease the risk compared with sulfonylurea or placebo, while DPP-4I appears to have neutral effect on cardiovascular risk.